MORTALITY IN THE PEDIATRIC INTENSIVE CARE UNITS, EXPERIENCE FROM SAUDI ARABIA - Elhag El Awad, Mohamed; Abbag, Fuad l. (Gezira Journal of Health Sciences; Vol 2 No 2 (2006), 2006)
This study was conducted to deternine the pediatric intensive care mortality in the Southwestern region of Saudi Arabia. The mortality rate was found to be 9.3% of all admitted cases. The mean age was 36.9 months. Children below 2 years of age constituted 64.3% of the total. The study showed multi system involvement accounted for 31.0% of the cases as the immediate cause leading to mortality. In this category sepsis was the commonest leading individual cause accounting for 26.2% of the cases. The underlying primary condition showed CNS involvement in 23.8% of the cases, followed by CVS & GIT (11.9% each.) In conclusion: children dying in the PICD are likely to have multi system failure as the immediate cause of death, while their primary underlying disease is likely to be in the CNS, GIT or CVS.